How does sex matter? Behavior, stress and animal models of neurobehavioral disorders. (May 2017) - Palanza, Paola; Parmigiani, Stefano
Highlights: Several neurobehavioral disorders exhibit sex differences in vulnerability, incidence and treatment response. Most translational neuroscience experiments use only male mice or rats. Mice show sexually differentiated responses to environmental, social and developmental factors. A sex-specific vulnerability to stress and related neurobehavioral disorders exists. Data obtained in males may be irrelevant for inferring psychopathology and treatments for females. Abstract: Many aspects of brain functioning exhibit important sex differences that affect behavior, mental health and mental disorders. However, most translational neuroscience research related to animal models of neurobehavioral disorders are carried out in male animals only. Based on published data from our laboratory on the House mouse, we discuss the following issues: (1) sex differences in social behavior of wild-derived mice; (2) artificial selection of laboratory strains and its consequences on social and reproductive competition; (3) sex-dependent effects of common experimental procedures; (4) differential effects of developmental events: the case of endocrine disruption; (5) implications for female models of stress and neurobehavioral disorders. Altogether, this review of data outline the marked differences of male and female responses to different social challenges and evinces the current lack of a relevant female mouse model of social stress. Whilst animal modelling is an important approach towards understanding mechanisms of neurobehavioral disorders, it is evident that data obtained in males may be irrelevant for inferring psychopathology and efficacy of pharmacological treatments for females.